Penanaman Karakter Disiplin dan Kerja Keras dalam Pembelajaran pada Mata Pelajaran Ekonomi Kelas XI di MAN Nglawak Kertosono: Penelitian - Tiara Nur’aini; Parham Taufik; A. Noer Chalifah Ramadhany (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The character of the nation is an important aspect of the quality of human resources (HR) in Indonesia because the quality of the nation's character determines the progress of a nation. A high-quality character needs to be formed and nurtured from an early age. Early childhood is a critical period for the formation of a person's character. According to Freud, the failure to instill good personality traits at an early age will shape a problematic personality in adulthood. The success of parents in educating their children to overcome personality conflicts in early childhood is crucial to the child’s success in social life in adulthood. The purpose of this research is to examine the instillation of discipline and hard work in the learning process of economics subjects at MAN Nglawak Kertosono. This research uses a descriptive qualitative approach, which involves written or spoken words from individuals and observed behaviors. The data collection methods used are interviews, observations, and documentation. The instillation of character at MAN Nglawak Kertosono, particularly in economics learning, is when the teacher incorporates characters relevant to the material being studied and the methods used during the teaching and learning process.